2011
DOI: 10.1152/jn.00814.2010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between size and latency of action potentials in human muscle sympathetic nerve activity

Abstract: We employed a novel action potential detection and classification technique to study the relationship between the recruitment of sympathetic action potentials (i.e., neurons) and the size of integrated sympathetic bursts in human muscle sympathetic nerve activity (MSNA). Multifiber postganglionic sympathetic nerve activity from the common fibular nerve was collected using microneurography in 10 healthy subjects at rest and during activation of sympathetic outflow using lower body negative pressure (LBNP). Burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
93
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(105 citation statements)
references
References 27 publications
(42 reference statements)
12
93
0
Order By: Relevance
“…Briefly, this technique uses a continuous wavelet transform (CWT) for AP detection. The CWT used a "mother wavelet" that was adapted to an actual average AP waveform constructed from physiological recordings of postganglionic sympathetic APs (i.e., matched mother wavelet had the same morphology as a physiological sympathetic AP; Salmanpour et al 2010). The designing process involves 1) detecting APs from the filtered raw MSNA signal and averaging them to build a mean AP template, and 2) matching the amplitude and the phase of the new mother wavelet to that of the mean AP template in the frequency domain .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, this technique uses a continuous wavelet transform (CWT) for AP detection. The CWT used a "mother wavelet" that was adapted to an actual average AP waveform constructed from physiological recordings of postganglionic sympathetic APs (i.e., matched mother wavelet had the same morphology as a physiological sympathetic AP; Salmanpour et al 2010). The designing process involves 1) detecting APs from the filtered raw MSNA signal and averaging them to build a mean AP template, and 2) matching the amplitude and the phase of the new mother wavelet to that of the mean AP template in the frequency domain .…”
Section: Methodsmentioning
confidence: 99%
“…Extracted APs were grouped as overlapped (i.e., the summated signal of two co-occurring APs) or single APs based on their morphology (for a complete performance evaluation of our AP detection algorithm on overlapping APs, see Salmanpour et al 2010). Then, nonoverlapped APs were ordered based on peak-to-peak amplitude and histogram analysis was performed to separate APs into amplitudebased clusters based on Scott's rule (Scott 1979).…”
Section: Methodsmentioning
confidence: 99%
“…During programmed stimulation-induced PVCs in healthy humans, significant modifications in neural discharge were presented as an increase in the amplitude and duration of the sympathetic burst immediately after the PVC (post-PVC burst) (9). The size of a postganglionic sympathetic burst reflects the number of active axons firing in that multiunit recording (22,26), as well as the size of the action potentials (APs). Recent work from our laboratories indicates the presence of a latent subpopulation of postganglionic sympathetic axons that generate large APs, are present during larger bursts, reflect faster conduction velocities, and are recruited with higher probability during severe chemoreflex (30) or baroreflex stress (26).…”
mentioning
confidence: 99%
“…The size of a postganglionic sympathetic burst reflects the number of active axons firing in that multiunit recording (22,26), as well as the size of the action potentials (APs). Recent work from our laboratories indicates the presence of a latent subpopulation of postganglionic sympathetic axons that generate large APs, are present during larger bursts, reflect faster conduction velocities, and are recruited with higher probability during severe chemoreflex (30) or baroreflex stress (26). The expression of such a subpopulation of latent, but large, APs during post-PVC sympathetic bursts remains to be established.…”
mentioning
confidence: 99%
“…For example, in addition to the severe chemoreflex response discussed above, similar patterns have now been observed during -80 mmHg of LBNP (15) but less so during -60 mmHg lower body suction (236). Furthermore, in preliminary studies, Salmanpour et al (237) observed that all action potentials present at baseline exhibited faster conduction velocities during a Valsalva's maneuver, evidence perhaps for the possibility of malleable synaptic delays within the neural pathway.…”
Section: Characteristics Of Postganglionic Sympathetic Dischargementioning
confidence: 70%